GEJALA KECEMASAN PADA SISWA SEKOLAH MENENGAH KEJURUAN - Ardianto, Patuh (Universitas Pendidikan Ganesha, 2018)
Anxiety is an emotional state as a result of pressure experienced by individuals. Anxiety can be experienced by anyone no exception students who experience pressure in dealing with academic problems. This study aims to determine the symptoms and anxiety levels of students in vocational high schools. This study uses a descriptive approach with a total of 30 student respondents. Data collection techniques in this study used a questionnaire that adopted the Burn Anxiety Inventory. The results showed that students experience symptoms of anxiety at a moderate level ie students have anxious thoughts. These symptoms of anxiety can interfere with the learning process of students because at these levels of anxiety students become difficult to concentrate, daydream and worry about many things. Keywords: Anxiety, anxiety symptoms, anxiety level.